In Vitro Digestibility of Fermented Rice Straw Supplemented with Cassava Tuber and Leaves Using Ruminal Fluid of Bali Cattle - Noviandi, Cuk Tri (clo Convention Linkage, Inc., 2016)
igestibility of high ﬁber feed depends on cellulolytic microbes. In order to maximize the degradation of ﬁbrous feed, the growth of ruminal microbes is needed to be improved. One eﬀort to increase the microbe population in the rumen is by manipulating the adequacy of nutrients for their growth. Microbes in the rumen require energy and protein for their growth and development. A synchronized proteinto-energy ratio indicates optimal fermentation efficiency. Cattle fed only fermented rice straw may be able to provide energy from structural carbohydrates of the rice straw. However, since fermented rice straw also contains rapidly degraded N derived from urea that used in fermentation process, feedstuffs that contain rapidly degraded carbohydrates (non-structural carbohydrates) such as cassava tuber can be used. On the other hand, to synchronize the slowly degraded carbohydrate of rice straw, slow degraded protein source feedstuffs such as cassava leaves can be added. With a good balance of energy and protein availability in the rumen, an increase of microbial population as well as increasing volatile fatty acids (VFA) production in the rumen can be expected. Cassava as a local food commodity in Indonesia is abundant throughout the year. Cassava tuber is known as a good carbohydrate source that is degraded rapidly, while the leaves contain quite high crude protein (CP) which is ranged 20 - 36% (Askar, 1996). The rapidly degraded carbohydrates in cassava tuber and slowly degraded CP in cassava leaves are a good combination as additional feed for cattle fed fermented rice straw. Based on these, a research that focused on improving the in vitro digestibility of fermented rice straw basal feed by supplemented with cassava tubers and leaves was established.